Modeling of the synergetic effect of the goals of sustainable development and its impact on inclusive growth of the Republic of Côte d'Ivoire - T. A. Kulagovskaya; Y. Nannein (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. In order to achieve the goals of sustainable development and inclusive growth in African countries, it is necessary to look for such spending directions of funds allocated by international organizations that will have the maximum synergetic effect for national economic systems.Goal. In this regard, the purpose of the study is to assess the effectiveness of the assistance of international organizations to ensure and to find ways to increase it by searching for potential growth points.Materials and methods. In the course of the study, regression equations using the least squares method and models for representing direct acyclic graphs were used.Results and discussion. The results of the study showed that a number of factors, including the revival of economic growth, the presence of a stable macroeconomic environment, high prices for agricultural goods, as well as the needs of investors for diversification, combined with growing competition for foreign direct investment, have a direct impact on the formation of inclusive growth trajectories in the Republic of Côte d'Ivoire. From the point of view of the quality of public administration, improving sustainable development in the Republic of Côte d'Ivoire requires the allocation of additional resources for the implementation of infrastructure and social projects. improving the business and investment climate to attract more and more financing, especially in the field of ICT, in the form of foreign direct investment and the implementation of projects within the framework of public-private partnerships.Conclusion. Practice shows that in the Republic of Côte d'Ivoire, foreign aid works best when combined with sound economic policy, transparency, good governance, the interest of local authorities and the effective use of new technologies.